The Relation between Prevalence of Positive Anti-chlamydia Pneumonia Antibody Titers and Atherosclerotic Diseases - Payman Izadpanah; abbas abdollahi (Fasa University of Medical Sciences, 2019)
Background & Objectives: One of the most important of heart problems is related to the occurrence of atherosclerotic plaques. One of the underlying factors in this regard is bacterial infections. Many studies indicate the association between Chlamydia pneumoniae and the creation of plaques; it is one of the most important organisms in the development of coronary heart disease. The aim of this study was to investigate the association between the antibodies against Chlamydia pneumoniae and those relation with coronary atherosclerosis. Materials & Methods: In this descriptive case-control study, serum samples were collected from two groups of patients (108 patients) and healthy subjects (108 persons). Anti-Chlamydia pneumonia antibody titers were evaluated; patients under study were diagnosed with acute myocardial infarction. Both groups were matched in terms of the age and sex to reduce possible interactions. Results: In the evaluation of IgG antibody titers by ELISA and comparison between the two groups, the positive titers were 88.2% in the case group and 60.5% in the healthy subjects; this percentage was 74.6% in all subjects. The results of the two groups were statistically significant (P ≤ 0.005). Conclusion: Regarding the significance of the results in comparison between the patient and the control group, it can be argued that the presence of Chlamydia pneumonia can have a significant relationship with the development of atherosclerotic plaques. Despite the controversial findings in this regard, precise molecular studies can reveal possible mechanisms for the association of bacterial infections and the development of atherosclerosis.